Art, music, and play as a teaching aid: applying creative uses of Universal Design for Learning in a prison science class - Heron, Philip J.; Crameri, Fabio; Canaletti, Elisabetta Febe; Harrison, Dalton; Hashemi, Sara; Leigh, Phoenix; Narayan, Sophia; Osowski, Kiona; Rantanen, Rosa; Williams, James A. (Frontiers in Education, 2025)
Science, technology, engineering, and mathematics (STEM) subjects can be rigid in their teaching structure, creating barriers to education for students with more complex learning needs. As a result, there has been an increased need for compassionate pedagogy and adaptive education practices to provide multi-modal learning experiences—often referred to as Universal Design for Learning (UDL). Here, we outline our work in teaching science in prison that applies UDL principles to create different educational access points which are not solely focused on rote learning and reading text (which some students struggle with). We use creative practices, including art, music, and play, as a teaching aid for science subjects such as climate change, sleep, and space exploration. The key findings here being that the application of UDL principles combined to produce a positive classroom experience in a science class—with students feeling more that science is for everyone of every neurotype. Although our work here is tailored to the restrictive prison environment, the application of its core principles to education are fundamental practices that could be beneficial to a wide audience.